Analisis Kelayakan Proyek Penggantian Mesin Otomasi pada PT. X - Eunike Apriliana Hartanti Mursalim; Felecia Felecia; Karina Agustin (Jurnal Titra, 2022)
PT. X is one of the transformer manufacturers in Indonesia. The difference in standard time at each workstation causes a bottleneck on the Core Coil Assembly (CCA) line resulting in late demand fulfillment. Coil LV has the longest processing time among others, therefore a semi automated machine replacement project is carried out to reduce the processing time. The purpose of this research is to find whether replacement on semi automated machine is the best option to be implemented for coil LV workstation. A Break Even Point (BEP) analysis will be used to compare the current state (manual machine) with two alternatives project (combination of semi automated machine). BEP value of alternative 1 is 2,292 units, while alternative 2 is 2,647 units. However, the replacement project is not feasible to be implemented this year because the use of manual machine has a lower cost to meet the demand of 1,601 units. Actually, the optimal capacity for semi automated machines is 8 coil units per shift, so the company can increase the output capacity by reviewing the number of demands.